Detection of epstein-barr virus in lower gastrointestinal tract lymphomas - Yunos, Asmah M.; ]aafar, Hasnan; ldris, Fauziah M.; Kaur, Gurjeet (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2006)
Background: Many studies in the literature have shown that Epstein-Barr virus (EBV) is associated with several human lymphoid and epithelial malignancies. However, the prevalence of EBV in non-Hodgkin lymphoma (NHL) of the lower gastrointestinal (Gl) tract has not been fully elucidated. Aim: The aim of this study was to determine the presence and distribution of EBV in formalin-fixed paraffin-embedded tissue samples obtained from 18 Malaysian patients diagnosed with NHL of the lower GI tract. Methods: The GI tract lymphoma tissue samples analyzed for the presence of EBV were divided into the following groups: NHL of the smalJ intestine (seven cases); NHL of the ileocecum {ten cases); and NHL of the rectum {one case). The presence ofEBV-encoded RNA (EBER) in all of the above tissue samples was tested for using conventional in situ hybridization technology. · Results: Two of 18 cases (11.1%) ofNin.. of the lowerGI tract demonstrated positive signals forEBVIEBER. In the first positive case, EBV lEBER signals were located in lymphoma cells in the serosa layer of the small intestine. In the second EBVIEBER-positive case, EBVIEBER signals were detected in diffuse B-celllymphoma of the ileocecum. Conclusion: These findings demonstrate a rare association between EBV and lower GI tract lymphomas in this group of Malaysian patients.